2006
DOI: 10.1111/j.1365-2249.2006.03111.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory oligodeoxynucleotide fromBifidobacterium longumsuppresses Th2 immune responses in a murine model

Abstract: SummaryWe have reported previously that novel immunostimulatory sequence (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 34 publications
(37 reference statements)
4
49
1
Order By: Relevance
“…It has been reported that some probiotics inhibit IgE production through improvement of Th1/Th2 imbalance by inducing production of Th1-type cytokines and suppressing production of Th2-type cytokine (IL-4) Yoshida et al, 2010). On the other hand, it has also been reported that some probiotics suppress the excess production of IgE and the development of allergic inflammation through the suppression of excessive Th2 cell response rather than by inducing production of Th1-type cytokines (Iwabuchi et al, 2007;Iwabuchi et al, 2009;Kanzato et al, 2008;Niers et al, 2005;Takahashi et al, 2006). It has been reported that one strain of Bifidobacterium suppresses the production of Th2 cell-attracting chemokines and that one strain of LAB induces Th2 cell apoptosis (Iwabuchi et al, 2009;Kanzato et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that some probiotics inhibit IgE production through improvement of Th1/Th2 imbalance by inducing production of Th1-type cytokines and suppressing production of Th2-type cytokine (IL-4) Yoshida et al, 2010). On the other hand, it has also been reported that some probiotics suppress the excess production of IgE and the development of allergic inflammation through the suppression of excessive Th2 cell response rather than by inducing production of Th1-type cytokines (Iwabuchi et al, 2007;Iwabuchi et al, 2009;Kanzato et al, 2008;Niers et al, 2005;Takahashi et al, 2006). It has been reported that one strain of Bifidobacterium suppresses the production of Th2 cell-attracting chemokines and that one strain of LAB induces Th2 cell apoptosis (Iwabuchi et al, 2009;Kanzato et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has also been reported that some probiotics decrease IgE production by suppressing excess production of Th2-type cytokine rather than by inducing production of Th1-type cytokines to ameliorate development of type-1 allergies (Iwabuchi et al, 2007;Iwabuchi et al, 2009;Kanzato et al, 2008;Niers et al, 2005;Takahashi et al, 2006). Shinshu University.…”
Section: Introductionmentioning
confidence: 99%
“…18,19) In plasmacytoid (lymphoid) dendritic cells, IFN-/ is produced by recognition of the bacterial body via Toll like receptor (TLR). 20) Based on these findings, we speculate that B. longum BB536 is recognized by lymphoid dendritic cells via TLR-2 and/or TLR-9, [21][22][23] resulting in the release of IFN-/ and subsequently activation of NK cells. In addition, since neutrophils also constantly secret IFN-/, which exerts autocrine action on the neutrophils themselves, we speculate that the increase in neutrophilic function (bactericidal activity) is also an immunostimulatory effect induced by B. longum BB536.…”
Section: Discussionmentioning
confidence: 99%
“…Both cytokines are TH2-derived, with IL-4 acting on Bcells to induce class-switching and on mast cells to induce degranulation and further cytokine production and IL-5 inducing eosinophil degranulation. Specific strains found to inhibit IL-4 and IL-5 production include L. casei (Schiffer et al, 2009), L. rhamnosus (Ghadimi et al, 2008), B. longum (Takahashi et al, 2006) and B. infantis (Dev et al, 2008).…”
Section: Discussionmentioning
confidence: 99%